2012
DOI: 10.1159/000339181
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of Echinodorus macrophyllus Micheli on Gentamicin-Induced Nephrotoxicity in Rats

Abstract: Background/Aims: Leaves of Echinodorus macrophyllus (EM), from the Alismataceae family, have been used in Brazilian folk medicine for their anti-inflammatory and diuretic properties. In this work, the diuretic and nephroprotective activities of crude extracts of EM were evaluated. Methods: Normal Wistar rats were given 0.9% NaCl containing either EM (10–300 mg/kg), furosemide (13 mg/kg) or arginine vasopressin (0.2 mg/kg). Thereafter, the rats were individually housed in metabolic cages, and urine volume was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
10
0
3
Order By: Relevance
“…According to Portella et al 2012, the leaves of Echinodorus macrophyllus exert a nephroprotective effect in Wistar rats (Portella et al 2012). Brugiolo et al (2011) showed that the extract of E. grandiflorus was able to modulate allergic pulmonary inflammation, and it may also be useful as a potential therapeutic agent for asthma (Lessa et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…According to Portella et al 2012, the leaves of Echinodorus macrophyllus exert a nephroprotective effect in Wistar rats (Portella et al 2012). Brugiolo et al (2011) showed that the extract of E. grandiflorus was able to modulate allergic pulmonary inflammation, and it may also be useful as a potential therapeutic agent for asthma (Lessa et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The study describes the provision of Echinodorus macrophyllus on urine elimination, in a dose-dependent induction group with gentamicin, presented polyuria and decreased GFR. 19 Therefore, observation of urine volume did not significantly describe tubule damage in the kidney, thus not able to describe expected effects for nephrotoxicity. Internal environment regulation of body cells is primarily maintained by the kidney through glomerular filtration, reabsorption and emission by tubules, and also hydrogen particle exchange.…”
Section: Discussionmentioning
confidence: 96%
“…Various nephrotoxicity studies using aminoglycosides show urine output in early stages of acute renal failure is non-oliguria or polyuria, but creatinine and urea accumulation in the blood can still be detected. 5,7,19 In addition, many factors affecting urine volume may cause insignificant results in showing presence or absence of nephrotoxicity in kidneys. One study conducted by Portella et al favor the occurrence of polyuria in the gentamicin-induced group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with different nephrotoxic drugs such as gentamicin, radiocontrasts and other chemotherapeutics reinforce the significant role of oxidative injury in nephrotoxic acute kidney injury. (12,(16)(17)(18) Antioxidants are compounds that attenuate or inhibit the oxidation of cellular protein, lipid peroxidation of the cell membrane and injury of nucleic acids. (7) In this scenario are the medicinal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results of antioxidant protection of the Echinodorus macrophyllus were found in studies carried out with the model of acute kidney injury induced by gentamicin. (17) The administration of flavonoids has shown a protective effect on nephrotoxicity induced by cisplatin in rats by elevating creatinine clearance, reducing lipid peroxidation and inflammatory mediators. (20) A similar result was shown in a study with the Uncaria tomentosa phytomedicine in a model of ischemic acute renal injury.…”
Section: Discussionmentioning
confidence: 99%